Then she was gone : a novel - Jewell, Lisa (New York : Atria Books, 2018)
"Ten years after her teenage daughter disappears, a woman crosses paths with a charming single father whose young child feels eerily familiar, in this evocative, suspenseful drama from New York Times bestselling author Lisa Jewell--perfect for fans of Paula Hawkins and Liane Moriarty. Ellie Mack was the perfect daughter. She was fifteen, the youngest of three. She was beloved by her parents, friends, and teachers. She and her boyfriend made a teenaged golden couple. She was days away from an idyllic post-exams summer vacation, with her whole life ahead of her. And then she was gone. Now, her mother Laurel Mack is trying to put her life back together. It's been ten years since her daughter disappeared, seven years since her marriage ended, and only months since the last clue in Ellie's case was unearthed. So when she meets an unexpectedly charming man in a cafe, no one is more surprised than Laurel at how quickly their flirtation develops into something deeper. Before she knows it, she's meeting Floyd's daughters--and his youngest, Poppy, takes Laurel's breath away. Because looking at Poppy is like looking at Ellie. And now, the unanswered questions she's tried so hard to put to rest begin to haunt Laurel anew. Where did Ellie go? Did she really run away from home, as the police have long suspected, or was there a more sinister reason for her disappearance? Who is Floyd, really? And why does his daughter remind Laurel so viscerally of her own missing girl?"--
Originally published in 2017 in Great Britain.
Keywords: FICTION / Contemporary Women; FICTION / Suspense; FICTION / Family Life; Suspense fiction